AXL receptor tyrosine kinase as a therapeutic target in NSCLC - Okimoto, Ross A (Lung Cancer (Auckl), 2015)
The AXL receptor tyrosine kinase and its ligand, Gas6, regulate key processes in lung cancer growth, metastasis, and epithelial–mesenchymal transition-associated drug resistance. Gas6 and AXL expression have been correlated with poor prognosis and advanced clinical stage in patients with lung cancer, and targeting the Gas6/AXL pathway demonstrates antitumor activity, decreases cellular invasion, and restores sensitivity in de novo and acquired drug resistance models. These findings implicate AXL as a promising therapeutic target in lung cancer. In this review, we explore the role of AXL in lung cancer progression, from tumor development to disseminated disease, and highlight the current clinical landscape of anti-AXL therapeutics.